1989
DOI: 10.1182/blood.v73.4.1066.1066
|View full text |Cite
|
Sign up to set email alerts
|

In utero gene transfer and expression: a sheep transplantation model

Abstract: Retroviral-mediated gene transfer was used to insert a Neo R gene into fetal sheep hematopoietic cells obtained by exchange transfusion from lambs in utero. After gene transfer the cells were returned to the donor fetus. The lambs were examined after birth for the presence of a functioning Neo R gene. Of ten analyzable animals, six were positive for G418 resistant progenitor cells (CFU-Mix, CFU-C, BFU-E, CFU-E). Two animals were studied for extended periods of time: 8 and 24 months. Each has demonstrated a pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…After birth, the Neo R sequence was detected in marrow and blood of many of these animals by PCR, and many of the animals contained G418-resistant hematopoietic progenitors of erythroid (CFU-E, BFU-E), myeloid (CFU-GM), and mix (CFU-Mix) phenotype, suggesting that primitive HSC may have been transduced. That HSC were transduced was further substantiated by the continued presence of G418resistant progenitors and PCR positivity in two animals that were observed for up to 43 and 59 months after birth [25]. This and the results of the direct-vector injection approach reported previously [1] and described here demonstrate that an in utero approach to gene therapy could result in the transfer and long-term expression of the vector-encoded genes.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…After birth, the Neo R sequence was detected in marrow and blood of many of these animals by PCR, and many of the animals contained G418-resistant hematopoietic progenitors of erythroid (CFU-E, BFU-E), myeloid (CFU-GM), and mix (CFU-Mix) phenotype, suggesting that primitive HSC may have been transduced. That HSC were transduced was further substantiated by the continued presence of G418resistant progenitors and PCR positivity in two animals that were observed for up to 43 and 59 months after birth [25]. This and the results of the direct-vector injection approach reported previously [1] and described here demonstrate that an in utero approach to gene therapy could result in the transfer and long-term expression of the vector-encoded genes.…”
Section: Discussionsupporting
confidence: 74%
“…These trials have thus far demonstrated gene transfer and expression in significantly higher percentages of circulating leukocytes than previous trials performed on adult patients. Moreover, in vitro studies have demonstrated that more efficient gene transfer with retroviral vectors can occur in populations of hematopoietic progenitors from fetal donors when compared to adult cell populations [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simplistically, disruption of normal homeostatic barriers leads to "holes in the levy," resulting in the loss of homeostatic integrity of the bone marrow. These holes lead to hemorrhage of nonreticulated erythrocytes into the hematopoietic compartment of the marrow space [9,11,12], the escape of marrow elements to the peripheral circulation [13], and the circulation of hematopoietic stem and progenitor cells that normally reside in the bone marrow [14]. The spleen temporarily becomes a major site of hematopoiesis until homeostasis is restored in the marrow [15], and progenitors traffic from the marrow to the spleen [16].…”
Section: Introductionmentioning
confidence: 99%
“…The in vivo proliferation of retroviralmarked cord blood cells has been evaluated in the ovine system [74]. Anderson and colleagues isolated ovine fetal cord blood cells via cordocentesis, transduced the cells in vitro with a retrovirus encoding neo, and then returned the cells to the fetus.…”
Section: Transduction Of Cord Blood Hematopoietic Stem/progenitor Cellsmentioning
confidence: 99%